HEALTH SERVICES AND COMMUNITY SATISFACTION OF THE MARUSU HEALTH CENTER, MAROS REGENCY - Putri Z, Bintang Maharani; Yamin, Muh Nur; Sakawati, Herlina (Universitas Negeri Makassar, 2025)
This study aims to determine the effect of health service quality on community satisfaction at the marusu community health center, maros regency. The research method used is the quantitative survey method (survey research). The research sample was 368 people using incidental sampling technique (accidenta; sampling). Techniques using data using questionnaires and documentation. The data analysis to explain the effect between variables descriptively. The results showed that the level of public satisfaction was in the very good category of Technical Competence, Access to Services, Effectiveness, Human Relations, Efficiency, Continuity of Service, Security and Comfort. Community satisfaction is in the very satisfied category with indicators namely Service Procedures, Completion Time, Service Costs, Service Products, Facilities and Infrastructure, and Officer Competence. Based on data analysis, it shows that the quality of health services has a significant influence on community satisfaction at the Marusu community health center, Maros regency with a percentage level of influence 55,1%. This shows the importance of service quality so that service delivery can provide results in accordance with what the community expects